2018
DOI: 10.1186/s13643-018-0771-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative exercise therapy for gastrointestinal cancer patients: a systematic review

Abstract: BackgroundGastrointestinal cancer patients are susceptible to significant postoperative morbidity. The aim of this systematic review was to examine the effects of preoperative exercise therapy (PET) on patients undergoing surgery for GI malignancies.MethodsIn accordance with PRISMA statement, all prospective clinical trials of PET for patients diagnosed with GI cancer were identified by searching MEDLINE, Embase, Cochrane Library, ProQuest, PROSPERO, and DARE (March 8, 2017). The characteristics and outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 46 publications
(124 reference statements)
2
43
0
1
Order By: Relevance
“…34 Changes of this magnitude are associated with benefits in other clinical situations. 29,35 Reported rates of adherence to prehabilitation exercise programmes vary from 16 to 97%, 4 with an average of 70% adherence in home-based programmes. 36 To date, there is no standardised way to assess adherence to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Changes of this magnitude are associated with benefits in other clinical situations. 29,35 Reported rates of adherence to prehabilitation exercise programmes vary from 16 to 97%, 4 with an average of 70% adherence in home-based programmes. 36 To date, there is no standardised way to assess adherence to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is substantial heterogeneity in the content of prehabilitation programmes, but structured exercise is a major component of most studies. [2][3][4][5] Within this rapidly growing area of perioperative medicine, studies have shown that prehabilitation can increase fitness prior to surgery 4,6 and reduce post-operative complications. 7,8 Post-operative pneumonia is a wellacknowledged complication after oesophagectomy and is reported in up to 50% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed preliminary results regarding the possible effectiveness of a tele-prehabilitation in esophagogastric cancer patients scheduled for tumor resection. Physical prehabilitation aims to enhance preoperative functional capacity to prepare patients for surgery and have a positive impact on postoperative outcomes [40]. The 6MWT has been shown to be useful to evaluate preoperative physical status before esophageal resection [41].…”
Section: Discussionmentioning
confidence: 99%
“…With frailty and ill-health comes a lack of physical activity which can exacerbate perioperative morbidity (27). Exercise as part of a prehabilitation programme has been proposed to counteract functional decline and enhance patient performance as well as attenuating sarcopenia and limiting deconditioning associated with disease burden (28). Traditionally, the notion of bed rest was advocated in anticipation for surgery but we now know that sedentary behaviour is associated with loss of lean muscle mass, reduced physical function and aerobic capacity and insulin resistance (29).…”
Section: Presurgical Exercisementioning
confidence: 99%
“…In addition, a combination of aerobic exercise training with resistance training was effective in reversing sarcopenia in elderly individuals with a reduction in postoperative pulmonary complications. As well as enhancing cardiopulmonary fitness, exercise was also proposed to reduce fatigue and have desirable outcomes on QOL (28).…”
Section: Presurgical Exercisementioning
confidence: 99%